Cumulative mild head injury in rugby: a comparison of cognitive deficit and postconcussive symptomatology between schoolboy rugby players and non-contact sport controls - Beilinsohn, Taryn (Rhodes University, Faculty of Humanities, Department of Psychology, 2001)
This study investigates the cumulative effects of concussive and subconcussive mild head injury on the cognitive functioning of schoolboy rugby players. A comprehensive battery of neuropsychological tests and a self-report postconcussive questionnaire were administered to top level schoolboy rugby players (n=47), and a non-contact sport control group of top level schoolboy hockey players (n=34). Group comparisons of the percentage of individuals with cognitive deficit were carried out between i) the schoolboy rugby and the schoolboy hockey players, ii) the rugby forward and the rugby backline players; iii) the rugby forward and the schoolboy hockey players and, iv) the rugby backline and the schoolboy hockey players. Results on the neuropsychological test battery did not provide any substantial evidence of a higher level of neuropsychological impairment in the rugby players relative to the control group, or in the rugby forward players relative to the rugby backline players. Results obtained on the postconcussive symptom questionnaire provided tentative indications that the rugby players do report a greater frequency of postconcussive symptomatology. The symptoms most frequently reported were being easily angered, memory problems, clumsy speech and sleep difficulties. It was hypothesized that the absence of cognitive impairment in the schoolboy rugby players compared with that noted for professional players was due to their younger age, relatively high IQ and education level and a less intensive level of physical participation in the sport, and hence less accumulated exposure to the game, thereby decreasing their exposure to mild head injuries. From a theoretical perspective, these pre-existing conditions were considered to act as protective factors against reductions in brain reserve capacity and concomitant susceptibility to the onset of neuropsychological dysfunction.
Keywords: Rugby football injuries; Head -- Wounds and injuries -- Psychology; Head -- Wounds and injuries -- Complications; Brain damage